Imprint compositions having passivated nanoparticles and materials and processes for manufacturing the same
Patent Information
- Application Number
- KR1020237020247
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-18
- Filing Date
- 2021-11-16
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2041-11-16
Smart Images

Figure R1020237020247_ABST
Abstract
Description
Technology Field
[0001] The embodiments of the present disclosure generally relate to microelectronic processing, and more specifically, to imprint compositions and materials and related processes useful for nanoimprint lithography (NIL). Background Technology
[0002] Nano- and micro-patterning of nanoparticle imprints offers opportunities to develop nanomaterial-based electronic devices, energy devices, sensors, and other types of devices with nanometer-scale resolution. Currently available imprint materials include organic (high-index polymers) or inorganic-organic hybrid materials (sol-gels). Most imprint materials have a low refractive index (<1.7), along with numerous issues related to optical transparency in the visible region, optical resolution, processability, high shrinkage of imprinted features, and cost-effectiveness.
[0003] Therefore, improved imprint compositions, materials, and related processes are required.
[0004] The embodiments of the present disclosure generally relate to imprint compositions and materials and related processes useful for nanoimprint lithography (NIL). In one or more embodiments, an imprint composition is provided, and the imprint composition comprises a plurality of passivated nanoparticles, one or more solvents, a surface ligand, an additive, and an acrylate. Each passivated nanoparticle comprises a core and one or more shells, the core comprises one or more metal oxides, and the shell comprises one or more passivation materials.
[0005] In some embodiments, the passivation material of the shell comprises one or more atomic layer deposition (ALD) materials, one or more block copolymers, or one or more silicon-containing compounds. In one or more examples, the silicon-containing compound comprises one or more silanes, one or more silanols, one or more siloxanes, one or more silicons, derivatives thereof, or any combination thereof.
[0006] In other embodiments, a method for preparing an imprinted surface comprises the steps of placing, coating, or otherwise placing an imprint composition containing a plurality of passivated nanoparticles on a substrate, bringing the imprint composition into contact with a stamp having a pattern, converting the imprint composition into a porous nanoimprint film, and removing the stamp from the porous nanoimprint film. Brief explanation of the drawing
[0007] In a manner that the features listed above in the present disclosure can be understood in detail, a more detailed description of the present disclosure, which has been briefly summarized above, may be made with reference to embodiments, some of which are illustrated in the accompanying drawings. However, it should be noted that the accompanying drawings are merely illustrative of exemplary embodiments and should not be construed as limiting the scope of the present disclosure and allow for other equally valid embodiments.
[0008] FIGS. 1a through 1f illustrate cross-sectional views of a workpiece processed through a number of operations while preparing a nanoimprint film containing passivated nanoparticles according to one or more embodiments described and discussed herein.
[0009] FIG. 2 illustrates a front view of an optical device according to one or more embodiments described and discussed herein.
[0010] For ease of understanding, the same reference numbers have been used where possible to designate the same elements common to the drawings. It is considered that the elements and features of one or more embodiments may be beneficially incorporated into other embodiments. Specific details for implementing the invention
[0011] The embodiments of the present disclosure generally relate to imprint compositions and imprint materials useful for nanoimprint lithography (NIL). An imprint composition can be converted into an imprint material by applying heat and / or one or more types of radiation, such as light or microwaves. In one or more embodiments, the imprint composition contains one or more types of passivated nanoparticles, one or more solvents, one or more surface ligands, one or more additives, and one or more acrylates.
[0012] Each passivated nanoparticle (NP) may be one, two, or more shells arranged around a coated particle, such as a core. In some examples, the passivated nanoparticles may contain one or more types of surface ligands (e.g., ligated NPs or stabilized NPs) coupled to the outer surface of the passivated nanoparticles. The passivated nanoparticles may have one or more different shapes or geometric structures, such as spherical, elliptical, rod-shaped, cubic, wire-shaped, cylindrical, rectangular, or combinations thereof.
[0013] In one or more embodiments, each passivated nanoparticle comprises a core and one or more shells that contain, encapsulate, or otherwise coat the core. The core contains one or more metal oxides, and the shell contains one or more passivation materials. Typically, the core and the shell contain different materials. The core contains titanium oxide, niobium oxide, zirconium oxide, hafnium oxide, dopants thereof, or any combination thereof. In some examples, the shell contains one or more metal oxides or other materials different from the core. The passivation material contained in the shell may be or may include one or more atomic layer deposition (ALD) materials, a polymer material containing one or more block copolymers, or a passivation material containing one or more silicon-containing compounds.
[0014] The ALD material contained in the shell may be deposited on the core or outer shell layer by one or more ALD processes. In some examples, the particle to be coated by the passivation material is the core. In other examples, the particle to be coated by the passivation material is the outermost shell of a nanoparticle containing one or more shells disposed on the core. The ALD material may be silicon oxide, silicon nitride, silicon oxynitride, one or more metal oxides, one or more metal nitrides, one or more metal oxynitrides, dopants thereof, or any combination thereof, or may include them. Exemplary ALD materials may be silicon oxide, zirconium oxide, hafnium oxide, aluminum oxide, tantalum oxide, niobium oxide, nickel oxide, cobalt oxide, tungsten oxide, vanadium oxide, cerium oxide, tin oxide, indium oxide, hafnium zirconium oxide, hafnium titanium oxide, titanium zirconium oxide, silicon titanium oxide, silicon nitride, titanium nitride, aluminum titanium oxide, one or more of these dopants, or any combination thereof, or may include these. In one or more examples, the core contains titanium oxide, and the shell contains silicon oxide, zirconium oxide, niobium oxide, or any combination thereof. For example, the core contains titanium oxide, the first shell on the core contains silicon oxide, and the second shell on the first shell contains zirconium oxide. In other examples, the core contains niobium oxide, and the shell contains silicon oxide, zirconium oxide, or any combination thereof. In some examples, the core contains zirconium oxide, and the shell contains silicon oxide.
[0015] In some embodiments, the particles to be coated (e.g., core particles or nanoparticles containing one or more shells) are rotated and / or vibrated in a drum-type chamber while being sequentially exposed to chemical precursors during the ALD process. In other embodiments, the particles to be coated are placed on a substrate or otherwise positioned while being sequentially exposed to chemical precursors during the ALD process. The ALD process typically involves sequentially exposing the particles to a first precursor and a second precursor to deposit a binary compound. The first precursors may be one or more of silicon precursors, zirconium precursors, hafnium precursors, aluminum precursors, tantalum precursors, niobium precursors, nickel precursors, cobalt precursors, tungsten precursors, vanadium precursors, cerium precursors, tin precursors, indium precursors, or combinations thereof, or may include these. The second precursor may be one or more of oxygen precursors (or oxidizing agents), nitrogen precursors (or nitrating agents), or combinations thereof, or may include them. In other examples, the ALD process comprises sequentially exposing particles to a first precursor, a second precursor, a third precursor, and a second precursor to deposit a ternary or tertiary compound. The third precursor may be any of the precursors listed as the first precursors, and the third precursor is different from the precursor used as the first precursor.
[0016] In some embodiments, the passivation material of the shell is a polymer material containing one or more block copolymers. Exemplary block copolymers may be polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP), polystyrene b-polyethylene oxide (PS-b-PEO), polystyrene-b-polybutadiene (PS-b-PB), polystyrene b-polymethyl methacrylate (PS-b-PMMA), polystyrene-block-polybutadiene-block-polystyrene, one or more poloxamers, poly(isoprene-block-dimethylaminoethyl methacrylate) (PI-b-PDMAEMA), poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO), polymers thereof, derivatives thereof, or any combination thereof, or may include these.
[0017] In one or more examples, the block copolymers may be or comprise PS-b-P4VP having a molecular weight (MW) of PS of about 45 kDa to about 320 kDa and a MW of P4VP of about 27 kDa to about 70 kDa. In some examples, the poloxamer is a triblock copolymer containing a central hydrophobic block of polypropylene glycol flanked with two hydrophilic blocks of polyethylene glycol (PEG), e.g., a Pluronic having a MW of about 12 kDa to about 15 kDa, commercially available from BASF, SE. ® F127 is a poloxamer. In other examples, the poloxamer is a poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol), a synperonic having an MW of about 14 kDa to about 16 kDa, such as commercially available from Croda International, PLC. ® F108 is poloxamer.
[0018] Surface passivation can be achieved during the synthesis of nanoparticles or after the base nanoparticles are prepared. In one or more examples, the nanoparticles are dispersed in one or more solvents (at a concentration of about 5 wt% to about 50 wt% of NP relative to the solvent) to maintain dispersion quality. A polymer material (e.g., block copolymers) is dissolved at a concentration of about 2 wt% to about 10 wt% in a solvent that is miscible and compatible with the nanoparticle solvent. In in-phase modification, the polymer material may undergo hydrolysis, esterification, or hydrogen bonding to attach to the surface of the nanoparticles. The density of passivation is controlled by the concentration of the polymer material.
[0019] In other embodiments, the passivation material of the shell contains one or more silicon-containing compounds. The silicon-containing compound may be one or more of silanes, silanols, siloxanes, silicons, other silicon-containing compounds, derivatives thereof, or any combination thereof, or may include them. Exemplary silicon-containing compounds may be (3-acetamidopropyl)trimethoxysilane, octailtriethoxysilane, octyltrimethoxysilane, 3-(trimethoxysilyl)propyl methacrylate, propyltriethoxysilane, (3-acryloxypropyl)tris(trimethylsiloxy)silane, dimethyldiethoxysilane, polydimethylsiloxane, γ-glycidoxypropyltrimethoxysilane (GPMS), polydiphenylsiloxane, hexamethylcyclotrisiloxane, aminopropyltriethoxysilane, complexes thereof, derivatives thereof, or any combination thereof, or may include these.
[0020] The total passivated nanoparticles may have a size or diameter of about 2 nm, about 5 nm, about 8 nm, about 10 nm, about 12 nm, about 15 nm, about 20 nm, about 25 nm, about 30 nm, or about 35 nm to about 40 nm, about 50 nm, about 60 nm, about 80 nm, about 100 nm, about 150 nm, or about 200 nm. For example, the total passivated nanoparticles are about 2 nm to about 200 nm, about 2 nm to about 150 nm, about 2 nm to about 100 nm, about 2 nm to about 80 nm, about 2 nm to about 60 nm, about 2 nm to about 50 nm, about 2 nm to about 40 nm, about 2 nm to about 30 nm, about 2 nm to about 20 nm, about 2 nm to about 15 nm, about 2 nm to about 10 nm, about 10 nm to about 200 nm, about 10 nm to about 150 nm, about 10 nm to about 100 nm, about 10 nm to about 80 nm, about 10 nm to about 60 nm, about 10 nm to about 50 nm, about 10 nm to about 40 nm, about 10 nm to about 30 nm, about 10 nm to about 20 It may have a size or diameter of nm, about 10 nm to about 15 nm, about 50 nm to about 200 nm, about 50 nm to about 150 nm, about 50 nm to about 100 nm, about 50 nm to about 80 nm, or about 50 nm to about 60 nm.
[0021] The core of the passivated nanoparticle has a diameter of less than 100 nm, e.g., less than 80 nm, or less than 50 nm, e.g., about 2 nm, about 3 nm, about 5 nm, about 8 nm, about 10 nm, or about 12 nm to about 15 nm, about 18 nm, about 20 nm, about 25 nm, about 30 nm, about 35 nm, about 40 nm, about 45 nm, or about 50 nm.For example, the core is about 2 nm to about 50 nm, about 2 nm to about 45 nm, about 2 nm to about 40 nm, about 2 nm to about 35 nm, about 2 nm to about 30 nm, about 2 nm to about 28 nm, about 2 nm to about 25 nm, about 2 nm to about 22 nm, about 2 nm to about 20 nm, about 2 nm to about 18 nm, about 2 nm to about 15 nm, about 2 nm to about 12 nm, about 2 nm to about 10 nm, about 2 nm to about 8 nm, about 2 nm to about 5 nm, about 5 nm to about 50 nm, about 5 nm to about 45 nm, about 5 nm to about 40 nm, about 5 nm to about 35 nm, about 5 nm to about 30 nm, about 5 nm to about 28 nm, about 5 nm to about 25 nm, about It has a diameter of 5 nm to about 22 nm, about 5 nm to about 20 nm, about 5 nm to about 18 nm, about 5 nm to about 15 nm, about 5 nm to about 12 nm, about 5 nm to about 10 nm, about 5 nm to about 8 nm, about 10 nm to about 50 nm, about 10 nm to about 45 nm, about 10 nm to about 40 nm, about 10 nm to about 35 nm, about 10 nm to about 30 nm, about 10 nm to about 28 nm, about 10 nm to about 25 nm, about 10 nm to about 22 nm, about 10 nm to about 20 nm, about 10 nm to about 18 nm, about 10 nm to about 15 nm, or about 10 nm to about 12 nm.
[0022] The shell of the passivated nanoparticle has a thickness of about 0.1 nm, about 0.2 nm, about 0.5 nm, about 0.8 nm, about 1 nm, about 1.5 nm, about 2 nm, about 3 nm, about 5 nm, about 8 nm, or about 10 nm to about 12 nm, about 15 nm, about 18 nm, about 20 nm, about 25 nm, about 30 nm, about 35 nm, about 40 nm, or about 50 nm. For example, the shell is about 0.1 nm to about 50 nm, about 0.1 nm to about 40 nm, about 0.1 nm to about 30 nm, about 0.1 nm to about 25 nm, about 0.1 nm to about 20 nm, about 0.1 nm to about 18 nm, about 0.1 nm to about 15 nm, about 0.1 nm to about 12 nm, about 0.1 nm to about 10 nm, about 0.1 nm to about 8 nm, about 0.1 nm to about 5 nm, about 0.1 nm to about 3 nm, about 0.1 nm to about 2 nm, about 0.1 nm to about 1 nm, about 0.5 nm to about 40 nm, about 0.5 nm to about 30 nm, about 0.5 nm to about 25 nm, about 0.5 nm to about 20 nm, about 0.5 nm to about 15 nm, About 0.5 nm to about 10 nm, about 0.5 nm to about 8 nm, about 0.5 nm to about 5 nm, about 0.5 nm to about 3 nm, about 0.5 nm to about 2 nm, about 0.It has a thickness of 5 nm to about 1 nm, about 1 nm to about 40 nm, about 1 nm to about 30 nm, about 1 nm to about 25 nm, about 1 nm to about 20 nm, about 1 nm to about 18 nm, about 1 nm to about 15 nm, about 1 nm to about 12 nm, about 1 nm to about 10 nm, about 1 nm to about 8 nm, about 1 nm to about 5 nm, about 1 nm to about 3 nm, about 5 nm to about 50 nm, about 5 nm to about 40 nm, about 5 nm to about 30 nm, about 5 nm to about 25 nm, about 5 nm to about 20 nm, about 5 nm to about 18 nm, about 5 nm to about 15 nm, about 5 nm to about 12 nm, about 5 nm to about 10 nm, or about 5 nm to about 8 nm.
[0023] In some examples, the core has a diameter of about 2 nm to about 50 nm, and the shell has a thickness of about 0.1 nm to about 40 nm. In other examples, the core has a diameter of about 5 nm to about 40 nm, and the shell has a thickness of about 0.5 nm to about 30 nm. In some examples, the core has a diameter of about 10 nm to about 30 nm, and the shell has a thickness of about 1 nm to about 20 nm.
[0024] In one or more examples, the imprint composition contains passivated nanoparticles at a concentration of about 0.1 wt%, about 0.5 wt%, about 1 wt%, about 2 wt%, about 3 wt%, about 5 wt%, about 6 wt%, about 8 wt%, or about 10 wt% to about 12 wt%, about 15 wt%, about 18 wt%, about 20 wt%, about 22 wt%, about 24 wt%, about 25 wt%, about 28 wt%, about 30 wt%, about 32 wt%, about 35 wt%, about 38 wt%, or about 40 wt%. For example, the imprint composition comprises passivated nanoparticles in an amount of about 0.1 wt% to about 40 wt%, about 0.5 wt% to about 40 wt%, about 0.5 wt% to about 35 wt%, about 0.5 wt% to about 32 wt%, about 0.5 wt% to about 30 wt%, about 0.5 wt% to about 28 wt%, about 0.5 wt% to about 25 wt%, about 0.5 wt% to about 22 wt%, about 0.5 wt% to about 20 wt%, about 0.5 wt% to about 18 wt%, about 0.5 wt% to about 15 wt%, about 0.5 wt% to about 12 wt%, about 0.5 wt% to about 10 wt%, about 0.5 wt% to about 8 wt%, about 0.5 wt% to about 6 wt%, about 0.5 wt% to about 5 wt%, about 0.5 wt% to about 4 wt%, about 0.5 wt% to about 3 wt%, about 0.5 wt% to about 2 wt%, about 0.5 wt% to about 1.5 wt%, about 0.5 wt% to about 1 wt%, about 2 wt% to about 40 wt%, about 2 wt% to about 35 wt%, about 2 wt% to about 32 wt%, about 2 wt% to about 30 wt%, about 2 wt% to about 28 wt%, about 2 wt% to about 25 wt%, about 2 wt% to about 22 wt%, about 2 wt% to about 20 wt%, about 2 wt% to about 18 wt%, about 2 wt% to about 15 wt%, about 2 wt% to about 12 wt%, about 2 wt% to about 10 wt%, about 2 wt% to about 8 wt%, about 2 wt% to about 6 wt%, about 2 wt% to about 5 wt%, about 2 wt% to about 4 It contains at a concentration of wt%, about 2 wt% to about 3 wt%, about 5 wt% to about 40 wt%, about 5 wt% to about 35 wt%, about 5 wt% to about 32 wt%, about 5 wt% to about 30 wt%, about 5 wt% to about 28 wt%, about 5 wt% to about 25 wt%, about 5 wt% to about 22 wt%, about 5 wt% to about 20 wt%, about 5 wt% to about 18 wt%, about 5 wt% to about 15 wt%, about 5 wt% to about 12 wt%, about 5 wt% to about 10 wt%, about 5 wt% to about 8 wt%, or about 5 wt% to about 6 wt%.
[0025] In other embodiments, the imprint composition contains passivated nanoparticles at a concentration of about 40 wt%, about 50 wt%, about 55 wt%, about 60 wt%, about 62 wt%, or about 65 wt% to about 68 wt%, about 70 wt%, about 75 wt%, about 80 wt%, about 85 wt%, about 88 wt%, about 90 wt%, about 92 wt%, about 93 wt%, about 94 wt%, about 95 wt%, about 96 wt%, about 97 wt%, about 98 wt%, or more. For example, the imprint composition comprises passivated nanoparticles of about 40 wt% to about 98 wt%, about 50 wt% to about 95 wt%, about 50 wt% to about 90 wt%, about 50 wt% to about 80 wt%, about 50 wt% to about 75 wt%, about 50 wt% to about 70 wt%, about 50 wt% to about 65 wt%, about 50 wt% to about 60 wt%, about 50 wt% to about 55 wt%, about 60 wt% to about 95 wt%, about 60 wt% to about 90 wt%, about 60 wt% to about 80 wt%, about 60 wt% to about 75 wt%, about 60 wt% to about 70 wt%, about 60 wt% It contains at a concentration of about 65 wt%, about 70 wt% to about 95 wt%, about 70 wt% to about 90 wt%, about 70 wt% to about 80 wt%, or about 70 wt% to about 75 wt%.
[0026] The surface ligand may be one or more carboxylic acids, one or more esters, one or more amines, one or more alcohols, one or more silanes, salts thereof, complexes thereof, or any combination thereof, or may include them. Exemplary surface ligands may be oleic acid, stearic acid, propionic acid, benzoic acid, palmitic acid, myristic acid, methylamine, oleylamine, butylamine, benzyl alcohol, oleyl alcohol, butanol, octanol, dodecanol, octyltrimethoxysilane, octyltriethoxysilane, octenyltrimethoxysilane, octenyltriethoxysilane, 3-(trimethoxysilyl)propyl methacrylate, propyltriethoxysilane, salts thereof, esters thereof, complexes thereof, or any combination thereof, or may include them. In some examples, surface ligands are present at a concentration of about 8 wt% to about 50 wt% based on the weight of the passivated nanoparticles.
[0027] The imprint composition contains surface ligands at a concentration of about 0.5 wt%, about 1 wt%, about 2 wt%, about 3 wt%, about 5 wt%, about 7 wt%, about 8 wt%, or about 10 wt% to about 12 wt%, about 15 wt%, about 18 wt%, about 20 wt%, about 25 wt%, about 30 wt%, about 35 wt%, about 40 wt%, about 45 wt%, or about 50 wt%. For example, the imprint composition comprises surface ligands of about 0.5 wt% to about 50 wt%, about 1 wt% to about 50 wt%, about 3 wt% to about 50 wt%, about 5 wt% to about 50 wt%, about 5 wt% to about 40 wt%, about 5 wt% to about 35 wt%, about 5 wt% to about 30 wt%, about 5 wt% to about 25 wt%, about 5 wt% to about 20 wt%, about 5 wt% to about 15 wt%, about 5 wt% to about 10 wt%, about 10 wt% to about 50 wt%, about 10 wt% to about 40 wt%, about 10 wt% to about 35 wt%, about 10 wt% to about 30 wt%, about 10 It contains at a concentration of wt% to about 25 wt%, about 10 wt% to about 20 wt%, about 10 wt% to about 15 wt%, about 15 wt% to about 50 wt%, about 15 wt% to about 40 wt%, about 15 wt% to about 35 wt%, about 15 wt% to about 30 wt%, about 15 wt% to about 25 wt%, or about 15 wt% to about 20 wt%.
[0028] The solvent may be one or more nanoparticle dispersion solvents, one or more imprinting solvents, other types of solvents, or any combination thereof, or may include them. The nanoparticle dispersion solvent may be one or more glycol ethers, alcohols, acetates, esters thereof, salts thereof, derivatives thereof, or any combination thereof, or may include them. In some examples, the nanoparticle dispersion solvent may be one or more p-series glycol ethers, one or more e-series glycol ethers, or any combination thereof, or may include them. In one or more examples, the nanoparticle dispersion solvent contains propylene glycol methyl ether acetate (PGMEA). The imprinting solvent may be one or more alcohols, one or more esters, salts thereof, or any combination thereof, or may include them. In one or more examples, the imprinting solvent contains ethyl lactate.
[0029] In one or more examples, the imprint composition contains one or more solvents at a concentration of about 50 wt%, about 55 wt%, about 60 wt%, about 62 wt%, about 65 wt%, about 68 wt%, about 70 wt%, about 72 wt%, about 75 wt%, or about 80 wt% to about 83 wt%, about 85 wt%, about 87 wt%, about 88 wt%, about 90 wt%, about 92 wt%, about 94 wt%, about 95 wt%, about 97 wt%, or about 98 wt%. For example, the imprint composition comprises one or more solvents in an amount of about 50 wt% to about 98 wt%, about 60 wt% to about 98 wt%, about 60 wt% to about 95 wt%, about 60 wt% to about 90 wt%, about 60 wt% to about 88 wt%, about 60 wt% to about 85 wt%, about 60 wt% to about 83 wt%, about 60 wt% to about 80 wt%, about 60 wt% to about 78 wt%, about 60 wt% to about 75 wt%, about 60 wt% to about 72 wt%, about 60 wt% to about 70 wt%, about 60 wt% to about 68 wt%, about 60 wt% to about 65 wt%, about 60 wt% to about 63 wt%, about 70 wt% to about 98 wt%, about 70 wt% to about 95 wt%, about 70 wt% to about 90 wt%, about 70 wt% to about 88 wt%, about 70 wt% to about 85 wt%, about 70 wt% to about 83 wt%, about 70 wt% to about 80 wt%, about 70 wt% to about 78 wt%, about 70 wt% to about 75 wt%, about 70 wt% to about 72 wt%, about 80 wt% to about 98 wt%, about 80 wt% to about 95 wt%, about 80 wt% to about 90 wt%, about 80 wt% to about 88 wt%, about 80 wt% to about 85 It contains at a concentration of wt%, about 80 wt% to about 83 wt%, or about 80 wt% to about 82 wt%.
[0030] In some embodiments, the imprint composition contains a nanoparticle dispersion solvent at a concentration of about 0.5 wt%, about 0.8 wt%, about 1 wt%, about 1.5 wt%, about 2 wt%, about 2.5 wt%, about 3 wt%, about 3.5 wt%, about 4 wt%, about 5 wt%, or about 6 wt% to about 7 wt%, about 8 wt%, about 10 wt%, about 12 wt%, about 14 wt%, about 15 wt%, about 18 wt%, about 20 wt%, or about 25 wt%. For example, the imprint composition comprises a nanoparticle dispersion solvent in an amount of about 0.5 wt% to about 20 wt%, about 1 wt% to about 20 wt%, about 1 wt% to about 18 wt%, about 1 wt% to about 15 wt%, about 1 wt% to about 13 wt%, about 1 wt% to about 12 wt%, about 1 wt% to about 11 wt%, about 1 wt% to about 10 wt%, about 1 wt% to about 8 wt%, about 1 wt% to about 7 wt%, about 1 wt% to about 6 wt%, about 1 wt% to about 5 wt%, about 1 wt% to about 4 wt%, about 1 wt% to about 3 wt%, about 5 wt% to about 20 wt%, and about 5 wt% to about 18 It contains at a concentration of wt%, about 5 wt% to about 15 wt%, about 5 wt% to about 13 wt%, about 5 wt% to about 12 wt%, about 5 wt% to about 11 wt%, about 5 wt% to about 10 wt%, about 5 wt% to about 8 wt%, about 5 wt% to about 7 wt%, about 5 wt% to about 6 wt%, about 8 wt% to about 20 wt%, about 8 wt% to about 18 wt%, about 8 wt% to about 15 wt%, about 8 wt% to about 13 wt%, about 8 wt% to about 12 wt%, about 8 wt% to about 11 wt%, about 8 wt% to about 10 wt%, or about 8 wt% to about 9 wt%.
[0031] In other embodiments, the imprint composition contains an imprinting solvent at a concentration of about 50 wt%, about 55 wt%, about 60 wt%, about 62 wt%, about 65 wt%, about 68 wt%, or about 70 wt% to about 72 wt%, about 75 wt%, about 78 wt%, about 80 wt%, about 82 wt%, about 83 wt%, about 85 wt%, about 87 wt%, about 88 wt%, about 90 wt%, or about 95 wt%. For example, the imprint composition comprises an imprinting solvent of about 50 wt% to about 95 wt%, about 60 wt% to about 95 wt%, about 60 wt% to about 90 wt%, about 60 wt% to about 88 wt%, about 60 wt% to about 85 wt%, about 60 wt% to about 83 wt%, about 60 wt% to about 80 wt%, about 60 wt% to about 78 wt%, about 60 wt% to about 75 wt%, about 60 wt% to about 72 wt%, about 60 wt% to about 70 wt%, about 60 wt% to about 68 wt%, about 60 wt% to about 65 wt%, about 60 wt% to about 63 wt%, and about 70 wt% to about 98 wt%, about 70 wt% to about 95 wt%, about 70 wt% to about 90 wt%, about 70 wt% to about 88 wt%, about 70 wt% to about 85 wt%, about 70 wt% to about 83 wt%, about 70 wt% to about 80 wt%, about 70 wt% to about 78 wt%, about 70 wt% to about 75 wt%, about 70 wt% to about 72 wt%, about 75 wt% to about 98 wt%, about 75 wt% to about 95 wt%, about 75 wt% to about 90 wt%, about 75 wt% to about 88 wt%, about 75 wt% to about 85 wt%, about 75 wt% to about 83 It contains at a concentration of wt%, about 75 wt% to about 80 wt%, or about 75 wt% to about 78 wt%.
[0032] The additive may be one or more perfluoroalkyl ethers, one or more polyglycols, one or more fatty acids, one or more silanes, one or more siloxanes, or any combination thereof, or may comprise them. Exemplary additives are fluorosurfactants, fluoro-additives, and / or fluorocarbons (e.g., CAPSTONE available from DuPont). ® FS-66 or FS-68 fluorosurfactant), glycolic acid ethoxylate oleyl ether, polyethylene glycol, polypropylene glycol, lauric acid, myristic acid, stearic acid, palmitic acid, dimethyldiethoxysilane, polydimethylsiloxane, polydiphenylsiloxane, hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, silanol-terminated polydimethylsiloxane, vinyl-terminated polydimethylsiloxane, 1,2-propanediol, salts thereof, esters thereof, complexes thereof, or combinations thereof, or may include these. The additive may be one or more diols, one or more alcohols having three or more alcohol groups, or any combination thereof, or may include these. In one or more examples, the additive contains 1,2-propanediol. In some examples, the additive is present at a concentration of about 0.01 wt% to about 2.5 wt% based on the weight of the passivated nanoparticles.
[0033] The imprint composition contains the additive at a concentration of about 0.01 wt%, about 0.05 wt%, about 0.1 wt%, about 0.2 wt%, about 0.3 wt%, about 0.5 wt%, about 0.8 wt%, or about 1 wt% to about 1.2 wt%, about 1.5 wt%, about 1.8 wt%, about 2 wt%, about 2.5 wt%, about 3 wt%, about 3.5 wt%, about 4 wt%, about 5 wt%, about 6 wt%, about 8 wt%, or about 10 wt%. For example, the imprint composition comprises an additive in an amount of about 0.01 wt% to about 10 wt%, about 0.01 wt% to about 8 wt%, about 0.01 wt% to about 5 wt%, about 0.01 wt% to about 4 wt%, about 0.01 wt% to about 3 wt%, about 0.01 wt% to about 2 wt%, about 0.01 wt% to about 1 wt%, about 0.01 wt% to about 0.5 wt%, about 0.01 wt% to about 0.1 wt%, about 0.01 wt% to about 0.05 wt%, about 0.1 wt% to about 10 wt%, about 0.1 wt% to about 8 wt%, about 0.1 wt% to about 5 wt%, about 0.1 wt% to about It contains at a concentration of 4 wt%, about 0.1 wt% to about 3 wt%, about 0.1 wt% to about 2 wt%, about 0.1 wt% to about 1 wt%, about 0.1 wt% to about 0.5 wt%, about 1 wt% to about 10 wt%, about 1 wt% to about 8 wt%, about 1 wt% to about 5 wt%, about 1 wt% to about 4 wt%, about 1 wt% to about 3 wt%, about 1 wt% to about 2 wt%, or about 1 wt% to about 1.5 wt%.
[0034] Acrylates may be one or more methacrylates, one or more ethyl acrylates, one or more propyl acrylates, one or more butyl acrylates, one or more monofunctional acrylates, one or more difunctional acrylates, one or more trifunctional acrylates, other polyfunctional acrylates, or any combination thereof, or may include them. Exemplary acrylates may be 3-(trimethoxysilyl)propyl methacrylate (3-MPS), 3-(trimethoxysilyl)propyl acrylate, di(ethylene glycol) methyl ether methacrylate, ethylene glycol methyl ether methacrylate, 2-ethylhexyl methacrylate, ethyl methacrylate, hexyl methacrylate, methacrylic acid, vinyl methacrylate, monomers thereof, polymers thereof, salts thereof, complexes thereof, or any combination thereof, or may include them. In some examples, acrylate is present at a concentration of about 0.05 wt% to about 10 wt% based on the weight of the passivated nanoparticles.
[0035] The imprint composition contains acrylate at a concentration of about 0.1 wt%, about 0.2 wt%, about 0.3 wt%, about 0.5 wt%, about 0.8 wt%, about 1 wt% to about 1.2 wt%, about 1.5 wt%, about 1.8 wt%, or about 2 wt%, about 2.2 wt%, about 2.3 wt%, about 2.5 wt%, about 2.8 wt%, about 3 wt%, about 3.2 wt%, about 3.5 wt%, about 3.8 wt%, about 4 wt%, about 5 wt%, about 6 wt%, about 8 wt%, about 10 wt%, about 12 wt%, about 15 wt%, about 18 wt%, or about 20 wt%. For example, the imprint composition comprises an acrylate of about 0.1 wt% to about 20 wt%, about 0.1 wt% to about 15 wt%, about 0.1 wt% to about 10 wt%, about 0.1 wt% to about 8 wt%, about 0.1 wt% to about 5 wt%, about 0.1 wt% to about 4 wt%, about 0.1 wt% to about 3 wt%, about 0.1 wt% to about 2 wt%, about 0.1 wt% to about 1 wt%, about 0.1 wt% to about 0.5 wt%, about 1 wt% to about 20 wt%, about 1 wt% to about 15 wt%, about 1 wt% to about 10 wt%, about 1 wt% to about 8 wt%, and about 1 wt% to about 5 wt%, about 1 wt% to about 4 wt%, about 1 wt% to about 3.5 wt%, about 1 wt% to about 3.2 wt%, about 1 wt% to about 3 wt%, about 1 wt% to about 2.8 wt%, about 1 wt% to about 2.5 wt%, about 1 wt% to about 2.3 wt%, about 1 wt% to about 2.2 wt%, about 1 wt% to about 2 wt%, about 1 wt% to about 2 wt%, about 1 wt% to about 1.8 wt%, about 1 wt% to about 1.5 wt%, about 1.8 wt% to about 20 wt%, about 1.8 wt% to about 15 wt%, about 1.8 wt% to about 10 wt%, about 1.8 wt% to about 8 wt%, about 1.It contains at a concentration of 8 wt% to about 5 wt%, about 1.8 wt% to about 4 wt%, about 1.8 wt% to about 3.5 wt%, about 1.8 wt% to about 3.2 wt%, about 1.8 wt% to about 3 wt%, about 1.8 wt% to about 2.8 wt%, about 1.8 wt% to about 2.5 wt%, about 1.8 wt% to about 2.3 wt%, about 1.8 wt% to about 2.2 wt%, or about 1.8 wt% to about 2 wt%.
[0036] In one or more examples, the imprint composition contains about 0.5 wt% to about 40 wt% of passivated nanoparticles, about 50 wt% to about 90 wt% of one or more solvents, about 5 wt% to about 40 wt% of surface ligands, about 0.01 wt% to about 5 wt% of additives, and about 0.1 wt% to about 10 wt% of acrylates. In other examples, the imprint composition contains about 1 wt% to about 25 wt% of passivated nanoparticles, about 60 wt% to about 85 wt% of one or more solvents, about 6 wt% to about 35 wt% of surface ligands, about 0.05 wt% to about 3 wt% of additives, and about 0.3 wt% to about 8 wt% of acrylates. In some examples, the imprint composition contains about 5 wt% to about 20 wt% of passivated nanoparticles, about 65 wt% to about 80 wt% of one or more solvents, about 7 wt% to about 31 wt% of surface ligands, about 0.09 wt% to about 1.5 wt% of additives, and about 0.5 wt% to about 6 wt% of acrylates.
[0037] The imprint composition may have a viscosity of about 1 cP, about 2 cP, about 3 cP, about 5 cP, about 8 cP, or about 10 cP to about 12 cP, about 15 cP, about 20 cP, about 25 cP, about 30 cP, about 40 cP, about 50 cP, or about 70 cP when measured at a temperature of 23°C. For example, when the imprint composition is measured at a temperature of 23°C, it is about 1 cP to about 70 cP, about 1 cP to about 50 cP, about 1 cP to about 40 cP, about 1 cP to about 30 cP, about 1 cP to about 20 cP, about 1 cP to about 10 cP, about 1 cP to about 5 cP, about 10 cP to about 70 cP, about 10 cP to about 50 cP, about 10 cP to about 40 cP, about 10 cP to about 30 cP, about 10 cP to about 20 cP, about 20 cP to about 70 cP, about 20 cP to about 50 cP, about 20 cP to about 40 cP, about 20 cP to about 30 cP, or about 20 cP to about 25 It can have a viscosity of cP. Methods for preparing an imprinted surface
[0038] In one or more embodiments, methods for preparing an imprinted surface, such as a NIL film, are provided. The imprinted surface is one or more exposed surfaces of the nanoimprint film described and discussed herein. The method comprises the steps of placing, coating, or otherwise positioning an imprint composition on one or more substrates, bringing the imprint composition into contact with a stamp having a pattern, converting the imprint composition into an imprint material (e.g., a nanoimprint film), and removing the stamp from the imprint material. In some examples, the substrate (e.g., a wafer) may be glass, quartz, silicon oxide, such as a glass substrate or a glass wafer, or may comprise these. In other examples, the substrate may be silicon, silicon-germanium, plastic, and / or other materials, or may comprise these. The imprint composition may have a refractive index of about 1.7 to about 2.0. The pattern transferred onto the stamp and the imprinted surface can be a one-dimensional pattern, a two-dimensional pattern, or a three-dimensional pattern.
[0039] FIGS. 1a through 1f illustrate cross-sectional views of a workpiece processed through a number of operations while preparing a nanoimprint film containing passivated nanoparticles, such as nanoimprint films according to one or more embodiments described and discussed herein. The nanoimprint film is formed on a substrate by an imprint process. The imprint process includes the steps of placing an imprint composition (104) containing passivated nanoparticles on a substrate (102) and aligning a stamp (120) on or adjacent to the imprint composition (104) (Fig. 1a). The imprint composition (104) is impressed or otherwise contacted with a stamp (120) having a pattern (Figs. 1b-1c). The imprint composition (104) is converted into a nanoimprint film (106) (Fig. 1d). In some examples, a curing process using heat and / or radiation (UV light) is used to convert the imprint composition (104) into a nanoimprint film (106). The stamp (120) is removed from the nanoimprint film (106) and left on the substrate (102) (Fig. 1e-1f).
[0040] In some examples, the imprint composition is deposited on a substrate by spin coating, drop casting, blade coating, and / or other coating processes. The imprint composition is deposited on the substrate as a film or layer having a predetermined thickness. The thickness of the imprint composition is about 50 nm, about 80 nm, about 100 nm, about 120 nm, about 150 nm, or about 200 nm to about 250 nm, about 300 nm, about 400 nm, about 500 nm, about 600 nm, about 800 nm, about 1,000 nm, about 1,200 nm, or greater. For example, the thickness of the imprint composition is about 50 nm to about 1,000 nm, about 100 nm to about 1,000 nm, about 200 nm to about 1,000 nm, about 400 nm to about 1,000 nm, about 500 nm to about 1,000 nm, about 600 nm to about 1,000 nm, about 800 nm to about 1,000 nm, about 50 nm to about 600 nm, about 100 nm to about 600 nm, about 200 nm to about 600 nm, about 400 nm to about 600 nm, about 500 nm to about 600 nm, about 500 nm to about 400 nm, about 100 nm to about 400 nm, about 200 nm to about 400 nm, or about 300 nm to about 400 nm.
[0041] An imprint composition is converted into an imprint material by exposing the imprint composition to heat, ultraviolet, infrared, visible light, microwave radiation, and / or any combination thereof. In one or more examples, when converting the imprint composition into an imprint material, the imprint composition is exposed to a light source having a wavelength of about 300 nm to about 365 nm. In other examples, when converting the imprint composition into an imprint material, the imprint composition is exposed to heat and maintained at a temperature of about 30°C to about 100°C for a time period of about 30 seconds to about 1 hour. In some examples, the imprint composition is exposed to heat and maintained at a temperature of about 50°C to about 60°C for a time period of about 1 minute to about 15 minutes.
[0042] In one or more embodiments, one or more acrylates of the imprint composition may be polymerized and / or oligomerized while producing the imprint material (e.g., curing or other conversion).
[0043] In one or more embodiments described and discussed herein, the imprint material contains or comprises inorganic oxide nanoparticles (about 1 wt% to about 95 wt%), a methacrylate or acrylate or chloro-acrylate binder (about 0.1 wt% to about 10 wt%), high-boiling point components, such as diols, fatty acids, amines (about 0.1 wt% to about 5 wt%), and an ether or acetate solvent (about 5 wt% to about 20 wt%) having an optimal viscosity (about 1 cP to about 50 cP at about 23°C). Imprint materials exhibit a high refractive index greater than 1.7 with optical transparency greater than 90% in the visible region at different weight percentages (about 1 wt% to about 50 wt%) and allow for high-resolution, large-area patterning with feature shrinkage rates of about 1% to about 30% (less than 1% in some examples). Nanoimprint lithography combined with high refractive index materials provides a unique pathway for fabricating printable devices by directly imprinting these functional materials. The patterned films possess the final desired optical functionality and do not require additional etching steps. This approach combines both the benefits of a top-down lithography process for fabricating micro / nanostructures with high control and the benefits of a bottom-up synthetic chemistry approach for designing and tuning the properties of the patterned films.
[0044] In other embodiments described and discussed herein, a passivated nanoparticle imprint composition is prepared, and the passivated nanoparticle imprint composition has a low viscosity of about 1 cP to about 50 cP (at about 23°C), a high refractive index, is optically transparent, and is easily processable. The imprint composition may comprise or contain passivated nanoparticles as described and discussed herein, disposed in about 1 wt% to about 80 wt% of a high-boiling point ether or acetate-based solvent. The imprint composition may comprise or contain one or more of a methacrylate or acrylate binder (about 0.1 wt% to about 10 wt%), a fatty acid (about 0.05 wt% to about 5 wt%), an amine (about 0.05 wt% to about 5 wt%), a PEG-based monomer (about 0.1 wt% to about 15 wt%), and a perfluoro- or siloxane dispersant acting as a surfactant (about 0.05 wt% to about 5 wt%). The final imprint composition remains optically transparent at room temperature (about 23°C) for more than 6 months and can be used with or without filtration.
[0045] In some embodiments, a scalable solvent-assisted soft NIL method is used to create large-area nanopatterned features and structures. This type of NIL uses polydimethylsiloxane (PDMS) or other silicon stamps, many of which can be produced from a single silicon master, each of which can be reused multiple times, thereby minimizing costs. Thus, the area of the imprinted structures is primarily limited only by the size of the original patterned master. Feature sizes smaller than 100 nm can be replicated using PDMS. Briefly, the imprint composition is filtered or dispensed directly onto the surface of the substrate. The substrate is spun to produce a film having a thickness of about 100 nm to about 400 nm. A PDMS mold is placed on the surface of the spin-on film and subsequently thermally cured at about 50°C to about 60°C. UV curing is performed at wavelengths of approximately 300 nm to approximately 365 nm, and at approximately 10 Jcm -2 Up to about 50 Jcm -2 It is performed using a light source with power. After the imprint composition is cured to create the imprint material, the PDMS stamp is removed in the direction of the grid or opposite to the direction of the grid. The released stamp is reused, and the imprint can be further cured by heat and / or UV processes to densify the material.
[0046] FIG. 2 illustrates a front view of an optical device (200) containing a nanoimprint film (106) as illustrated in FIG. 1f, according to one or more embodiments described and discussed herein. It should be understood that the optical device (200) described below is an exemplary optical device. In one or more embodiments, the optical device (200) is a waveguide combiner, such as an augmented reality waveguide combiner. In other embodiments, the optical device (200) is a planar optical device, such as a metasurface. The optical device (200) comprises a plurality of device structures (204). The device structures (204) may be nanostructures having sub-micro dimensions, such as nano-size dimensions, such as critical dimensions of less than 1 μm. In one or more embodiments, regions of the device structures (204) correspond to one or more gratings (202), such as grating regions (202a and 202b). In one or more embodiments, the optical device (200) includes a first grating region (202a) and a second grating region (202b), and each of the first grating regions (202a and 202b) contains a plurality of device structures (204).
[0047] The depth of the gratings (202) may vary across the grating regions (202a and 202b) of the embodiments described herein. In some embodiments, the depth of the gratings (202) may vary smoothly across the first grating region (202a) and the second grating region (202b). In one or more examples, the depth may be in the range of about 10 nm to about 400 nm across one of the grating regions. In some examples, the grating region (202a) may be in the range of about 20 mm to about 50 mm on a given side. Thus, in some examples, the angle of variation of the depth of the gratings (202) may be about 0.0005 degrees.
[0048] In the embodiments described herein, device structures (204) may be created using laser ablation. Laser ablation as used herein is used to create three-dimensional microstructures in the device material, or optionally, to create variable-depth structures on a sacrificial layer covering the device material as part of a variable-depth structure process. Using laser ablation to create optical structures (204) enables fewer processing operations and higher variable-depth resolution than conventional methods.
[0049] The embodiments of the present disclosure further relate to any one or more of the following Examples 1 to 24:
[0050] 1. An imprint composition comprising a plurality of passivated nanoparticles — each passivated nanoparticle comprises a core and a shell, the core comprises a metal oxide, and the shell comprises a passivation material —; one or more solvents; a surface ligand; an additive; and an acrylate.
[0051] 2. An imprint composition comprising a plurality of passivated nanoparticles ― each passivated nanoparticle comprises a core and a shell; the core comprises a metal oxide; the shell comprises a passivation material; the passivation material comprises an atomic layer deposition (ALD) material, a block copolymer, or a silicon-containing compound ―; one or more solvents; a surface ligand; an additive; and an acrylate.
[0052] 3. In the imprint composition according to Example 1 or Example 2, the core comprises titanium oxide, niobium oxide, zirconium oxide, hafnium oxide, dopants thereof, or any combination thereof.
[0053] 4. In the imprint composition according to any one of Examples 1 to 3, the passivation material of the shell includes an ALD material.
[0054] 5. In an imprint composition according to any one of Examples 1 to 4, the ALD material is selected from silicon oxide, zirconium oxide, hafnium oxide, aluminum oxide, tantalum oxide, niobium oxide, nickel oxide, cobalt oxide, tungsten oxide, vanadium oxide, cerium oxide, tin oxide, indium oxide, hafnium zirconium oxide, hafnium titanium oxide, titanium zirconium oxide, silicon titanium oxide, silicon nitride, titanium nitride, aluminum titanium oxide, dopants thereof, or any combination thereof, and the core and shell comprise different materials.
[0055] 6. In the imprint composition according to any one of Examples 1 to 5, the passivation material of the shell comprises a block copolymer.
[0056] 7. In an imprint composition according to any one of Examples 1 to 6, the block copolymer comprises polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP), polystyrene b-polyethylene oxide (PS-b-PEO), polystyrene-b-polybutadiene (PS-b-PB), polystyrene b-polymethyl methacrylate (PS-b-PMMA), polystyrene-block-polybutadiene-block-polystyrene, poloxamer, poly(isoprene-block-dimethylaminoethyl methacrylate) (PI-b-PDMAEMA), poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO), polymers thereof, or any combination thereof.
[0057] 8. In an imprint composition according to any one of Examples 1 to 7, the passivation material of the shell comprises a silicon-containing compound, and the silicon-containing compound comprises a silane, silanol, siloxane, silicon, or any combination thereof.
[0058] 9. In an imprint composition according to any one of Examples 1 to 8, the silicon-containing compound comprises (3-acetamidopropyl)trimethoxysilane, octyltriethoxysilane, octailtrimethoxysilane, 3-(trimethoxysilyl)propyl methacrylate, propyltriethoxysilane, (3-acryloxypropyl)tris(trimethylsiloxy)silane, dimethyldiethoxysilane, polydimethylsiloxane, γ-glycidoxypropyltrimethoxy-silane (GPMS), polydiphenylsiloxane, hexamethylcyclotrisiloxane, aminopropyltriethoxysilane, a complex thereof, or any combination thereof.
[0059] 10. In an imprint composition according to any one of Examples 1 to 9, the core has a diameter of about 2 nm to about 50 nm.
[0060] 11. In an imprint composition according to any one of Examples 1 to 10, the shell has a thickness of about 0.1 nm to about 40 nm.
[0061] 12. A method for forming a nanoimprint film, comprising the steps of: placing an imprint composition comprising a plurality of passivated nanoparticles on a substrate ― each passivated nanoparticle comprises a core and a shell; the core comprises a metal oxide; the shell comprises a passivation material; the passivation material comprises an ALD material, a block copolymer, or a silicon-containing compound, wherein the silicon-containing compound comprises a silane, a silanol, a silicon, a siloxane, derivatives thereof, or any combination thereof ―; bringing the imprint composition into contact with a stamp having a pattern; converting the imprint composition into a porous nanoimprint film; and removing the stamp from the porous nanoimprint film.
[0062] 13. In the method according to Example 12, the core comprises titanium oxide, niobium oxide, zirconium oxide, hafnium oxide, dopants thereof, or any combination thereof.
[0063] 14. In the method according to Example 12 or Example 13, the passivation material of the shell includes an ALD material.
[0064] 15. In a method according to any one of Examples 12 to 14, the ALD material is selected from silicon oxide, zirconium oxide, hafnium oxide, aluminum oxide, tantalum oxide, niobium oxide, nickel oxide, cobalt oxide, tungsten oxide, vanadium oxide, cerium oxide, tin oxide, indium oxide, hafnium zirconium oxide, hafnium titanium oxide, titanium zirconium oxide, silicon titanium oxide, silicon nitride, titanium nitride, aluminum titanium oxide, dopants thereof, or any combination thereof, and the core and shell comprise different materials.
[0065] 16. In the method according to any one of Examples 12 to 15, the passivation material of the shell comprises a block copolymer.
[0066] 17. In the method according to any one of Examples 12 to 16, the block copolymer comprises polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP), polystyrene b-polyethylene oxide (PS-b-PEO), polystyrene-b-polybutadiene (PS-b-PB), polystyrene b-polymethyl methacrylate (PS-b-PMMA), polystyrene-block-polybutadiene-block-polystyrene, poloxamer, poly(isoprene-block-dimethylaminoethyl methacrylate) (PI-b-PDMAEMA), poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO), polymers thereof, or any combination thereof.
[0067] 18. In the method according to any one of Examples 12 to 17, the passivation material of the shell comprises a silicon-containing compound.
[0068] 19. In the method according to any one of Examples 12 to 18, the silicon-containing compound comprises (3-acetamidopropyl)trimethoxysilane, octyltriethoxysilane, octailtrimethoxysilane, 3-(trimethoxysilyl)propyl methacrylate, propyltriethoxysilane, (3-acryloxypropyl)tris(trimethylsiloxy)silane, dimethyldiethoxysilane, polydimethylsiloxane, γ-glycidoxypropyltrimethoxy-silane (GPMS), polydiphenylsiloxane, hexamethylcyclotrisiloxane, aminopropyltriethoxysilane, a complex thereof, or any combination thereof.
[0069] 20. In the method according to any one of Examples 12 to 19, the core has a diameter of about 2 nm to about 50 nm.
[0070] 21. In the method according to any one of Examples 12 to 20, the shell has a thickness of about 0.1 nm to about 40 nm.
[0071] 22. In a method according to any one of Examples 12 to 21, the step of converting the imprint composition into an imprint material further comprises the step of exposing the imprint composition to a light source having a wavelength of about 300 nm to about 365 nm.
[0072] 23. In a method according to any one of Examples 12 to 22, the step of converting the imprint composition into an imprint material further comprises the step of heating the imprint composition to a temperature of about 50°C to about 60°C for a time period of about 1 minute to about 15 minutes.
[0073] 24. An imprint composition prepared, manufactured, or otherwise formed by a method according to any one of Examples 12 to 23.
[0074] Although the foregoing relates to embodiments of the present disclosure, other and additional embodiments may be devised without departing from the basic scope of the present disclosure, and the scope of the present disclosure is determined by the following claims. All documents described herein, including any priority documents and / or test procedures, are incorporated herein by reference, unless otherwise contrary to this specification. As is evident from the foregoing general description and specific embodiments, forms of the present disclosure have been illustrated and described, but various modifications may be made without departing from the spirit and scope of the present disclosure. Accordingly, the present disclosure is not intended to be limited by them. Likewise, the term “comprising” is considered synonymous with the term “including” for the purposes of U.S. law. Likewise, whenever the transition phrase “consisting” follows a composition, element, or group of elements, the same group of compositions or elements as the transition phrases “consisting essentially of,” “consisting of,” “selected from a group composed of,” or “is” following the composition, element, or enumeration of elements are considered, and the opposite is understood to be true.
[0075] Certain embodiments and features have been described using a series of numeric upper limits and a series of numeric lower limits. Unless otherwise indicated, it should be recognized that ranges are considered that include any combination of two values, e.g., a combination of any lower value and any upper value, a combination of any two lower values, and / or a combination of any two upper values. Specific lower limits, upper limits, and ranges appear in one or more of the claims below.
Claims
Claim 1 As an imprint composition, a plurality of passivated nanoparticles—each passivated nanoparticle comprising a core and a shell, wherein the core comprises a metal oxide and the shell comprises a passivation material, wherein the passivation material of the shell comprises an atomic layer deposition (ALD) material or a block copolymer, wherein where the passivation material of the shell comprises an ALD material, the ALD material is selected from silicon oxide, zirconium oxide, hafnium oxide, aluminum oxide, tantalum oxide, niobium oxide, nickel oxide, cobalt oxide, tungsten oxide, vanadium oxide, cerium oxide, tin oxide, indium oxide, hafnium zirconium oxide, hafnium titanium oxide, titanium zirconium oxide, silicon titanium oxide, silicon nitride, titanium nitride, aluminum titanium oxide, dopants thereof, or any combination thereof, wherein the core and the shell comprise different materials, and where the passivation material of the shell comprises a block copolymer. The above block copolymer comprises polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP), polystyrene b-polyethylene oxide (PS-b-PEO), polystyrene-b-polybutadiene (PS-b-PB), polystyrene b-polymethyl methacrylate (PS-b-PMMA), polystyrene-block-polybutadiene-block-polystyrene, poloxamer, poly(isoprene-block-dimethylaminoethyl methacrylate) (PI-b-PDMAEMA), poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO), polymers thereof, or any combination thereof; a surface ligand; an additive; and an acrylate, comprising an imprint composition. Claim 2 The imprint composition according to claim 1, wherein the core comprises titanium oxide, niobium oxide, zirconium oxide, hafnium oxide, dopants thereof, or any combination thereof. Claim 3 An imprint composition according to claim 1, further comprising one or more solvents. Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 delete Claim 8 delete Claim 9 The imprint composition according to claim 1, wherein the core has a diameter of about 2 nm to about 50 nm. Claim 10 In claim 9, the shell is an imprint composition having a thickness of about 0.1 nm to about 40 nm. Claim 11 delete Claim 12 A method for forming a nanoimprint film, comprising the step of disposing of an imprint composition comprising a plurality of passivated nanoparticles on a substrate ― each passivated nanoparticle comprises a core and a shell; said core comprises a metal oxide; said shell comprises a passivation material; And the passivation material comprises an atomic layer deposition (ALD) material, a block copolymer, or a silicon-containing compound, wherein the silicon-containing compound comprises a silane, silanol, silicon, siloxane, derivatives thereof, or any combination thereof; where the passivation material of the shell comprises an ALD material, the ALD material is selected from silicon oxide, zirconium oxide, hafnium oxide, aluminum oxide, tantalum oxide, niobium oxide, nickel oxide, cobalt oxide, tungsten oxide, vanadium oxide, cerium oxide, tin oxide, indium oxide, hafnium zirconium oxide, hafnium titanium oxide, titanium zirconium oxide, silicon titanium oxide, silicon nitride, titanium nitride, aluminum titanium oxide, dopants thereof, or any combination thereof; and the core and the shell comprise different materials; and where the passivation material of the shell comprises a block copolymer, the block copolymer Polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP), polystyrene b-polyethylene oxide (PS-b-PEO), polystyrene-b-polybutadiene (PS-b-PB), polystyrene b-polymethyl methacrylate (PS-b-PMMA), polystyrene-block-polybutadiene-block-polystyrene, poloxamer, poly(isoprene-block-dimethylaminoethyl methacrylate) (PI-b-PDMAEMA), poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO), polymers thereof, or any combination thereof, wherein the passivation material of the shell comprises a silicon-containing compound, wherein the silicon-containing compound is (3-acetamidopropyl)trimethoxysilane, octyltriethoxysilane,A method for forming a nanoimprint membrane, comprising: octailtrimethoxysilane, 3-(trimethoxysilyl)propyl methacrylate, propyltriethoxysilane, (3-acryloxypropyl)tris(trimethylsiloxy)silane, dimethyldiethoxysilane, polydimethylsiloxane, γ-glycidoxypropyltrimethoxysilane (GPMS), polydiphenylsiloxane, hexamethylcyclotrisiloxane, aminopropyltriethoxysilane, complexes thereof, or any combination thereof; contacting the imprint composition with a stamp having a pattern; converting the imprint composition into a porous nanoimprint membrane; and removing the stamp from the porous nanoimprint membrane. Claim 13 A method for forming a nanoimprint film according to claim 12, wherein the step of converting the imprint composition into an imprint material further comprises the step of exposing the imprint composition to a light source having a wavelength of about 300 nm to about 365 nm. Claim 14 A method for forming a nanoimprint film according to claim 12, wherein the step of converting the imprint composition into the imprint material further comprises the step of heating the imprint composition to a temperature of about 50°C to about 60°C for a time period of about 1 minute to about 15 minutes. Claim 15 A method for forming a nanoimprint film according to claim 12, wherein the core comprises titanium oxide, niobium oxide, zirconium oxide, hafnium oxide, a dopant thereof, or any combination thereof. Claim 16 delete Claim 17 delete Claim 18 delete Claim 19 delete Claim 20 A method for forming a nanoimprint film according to claim 12, wherein the core has a diameter of about 2 nm to about 50 nm and the shell has a thickness of about 0.1 nm to about 40 nm.
Citation Information
Patent Citations
Core / shell type metal oxide fine particle and photosensitive composition
JP2010208911A
Siloxane resin composition, transparent cured product using the same, transparent pixel, microlens, and solid-state imaging device
JP2016074870A
Laminate with high refractive index pattern, composition for forming high refractive index pattern, and method for forming high refractive index pattern
JP2016109983A
Curable formulation with high refractive index and its application in surface relief grating using nanoimprinting lithography
US20200249568A1
